Theotônio dos Santos (1936-2018) and the reconstruction of political economy of development - Domínguez-Martín, Rafael (Iberoamerican Journal of Development Studies, 2018)
This essay analyzes economic thought trajectory of the great Latin American intellectual Theotônio dos Santos in his vital context and the history of ideas, as well as his main contributions to the critical studies of development.
Keywords: development; dependence theory; planetary civilization; history of economic thought